Molecular Docking-Based Screening of Phenylpropanoids as Potential Antifungal Agents Against Magnaporthe oryzae - Fidelia Melissa Sihombing (CV. Truly Science Publishing, 2026)
Background: Rice blast disease caused by Magnaporthe oryzae leads to annual yield losses of 10–30%, exacerbated by fungicide resistance and environmental toxicity of synthetic chemicals. Phenylpropanoids have shown potential as eco-friendly antifungal agents, yet systematic molecular screening against key pathogenic targets remains limited. Aim: This study aimed to identify potential phenylpropanoid-based antifungal compounds targeting Isocitrate Lyase (ICL1) and MoErs1 proteins of M. oryzae through an in silico approach. Methods: A total of 317 phenylpropanoid-derived ligands were screened using molecular docking against ICL1 (PDB ID: 5e9f) and MoErs1 (PDB ID: 7vs2). Docking simulations were conducted using AutoDock Vina, followed by interaction analysis using LigPlot+ and PLIP to evaluate binding affinity and interaction patterns. Results: Six compounds, Vitisin A, Miyabenol A, Viniferol D, Suffruticosol A, Suffruticosol B, and Isohopeaphenol, demonstrated superior binding affinity (up to −11.57 kcal/mol) compared to commercial fungicides Edifenphos and Tricyclazole. These ligands formed stable complexes through hydrogen bonding, hydrophobic interactions, and π-stacking with key active-site residues of both target proteins. Conclusion: These findings suggest that selected phenylpropanoids have strong potential as multi-target antifungal agents against M. oryzae. This study provides a structural foundation for developing environmentally friendly biofungicides and contributes to sustainable crop protection strategies, although further experimental validation is required.